miR-137: A New Player in Schizophrenia - Yin, Jingwen (Molecular Diversity Preservation International (MDPI), 2014)
Schizophrenia is a complex genetic disease and characterized by affective, cognitive, neuromorphological, and molecular abnormalities that may have a neurodevelopmental origin. MicroRNAs (miRNAs) are critical to neurodevelopment and adult neuronal processes by modulating the activity of multiple genes within biological networks. MiR-137 as a brain-enriched microRNA, plays important roles in regulating embryonic neural stem cells (NSCs) fate determination, neuronal proliferation and differentiation, and synaptic maturation. Its dysregulation causes changes in the gene expression regulation network of the nervous system, thus inducing mental disorders. Recently, miR-137 has been confirmed as a gene related to schizophrenia susceptibility. In the following review, we summarize the expression pattern, epigenetic regulation and functions of miR-137. A more complete picture of the miR-137, which is dysregulated in psychiatric illness, may improve our understanding of the molecular mechanisms underlying schizophrenia.